Vision Loss following Small Incision Cataract Surgery: A Case Report - Chaudhary, Sushma; Gupta, Sharad; Singh, Sanjaykumar; Sharma, Hari; Yadav, Reena; Kamble, Vinit Kumar (Journal of Lumbini Medical College, 2021)
Introduction: Retro-bulbar block is still safe and widely employed anesthetic technique in large volume routine cataract surgery. Nevertheless, the procedure is not free of complication. Case report: A 48 years old man who had small incision cataract surgery of left eye under retro-bulbar block, had vision of hand movement close to face on his first postoperative day. He was given intracameral cefuroxime and subconjunctival gentamycin at the end of the surgery. Fundoscopy of the operated eye showed marked retinal whitening with cherry red spot in the posterior pole suggestive of cilio-retinal artery occlusion. Optical coherence tomography and optical coherence tomography angiography were done to support and confirm the diagnosis. Conclusion: Retinal artery occlusion secondary to retro-bulbar block or drug induced toxicity following routine cataract surgery is unusual and sometimes dreadful vision threatening complication can occur